Fuel subsidy in Nigeria: contexts of governance and social protest (2014)
Purpose – Fuel subsidy removal has become a recurring issue in Nigeria. Successive governments in the country have interfaced with this issue as they attempted to reform the economy and the petroleum downstream to reduce corruption and waste and make the sector more effective. Importantly however, fuel subsidy removals have always met opposition from the citizens and civil society organisations. The remit of this article is to bring original and current perspectives into the issue and trajectories of fuel subsidy, which has become a major problem in Nigeria’s development struggles. Previous works were dated and did not capture most recent popular uprising. The paper aims to discuss these issues. Design/methodology/approach – Purely primary, empirica and normative with primary insight. Findings – A major mechanism that must be put in place is popular and unpoliticized anti-corruption mechanisms and networks especially to sanitize the oil sector in the minimum. Also, government must demonstrate transparency and accountability across sectors and spending including at the government house. Sufficient palliatives like public transport and dedicated social services for the really poor is important before subsidy is implemented. Until these are done, government’s intention to successfully Remove Subsidy For Development (RS4D) may be a mirage! Research limitations/implications – This paper presents details of an international work with evolving issues. Originality/value – The paper argues that subsidy removal that will lead to high fuel prices appears unjustified given the wide income gap between workers in Nigeria and those in other oil-producing nations.